Numerical and experimental investigation of a vibration system with non-ideal vibration source - Gonçalves, Paulo J. P. [UNESP] (2014)
An excitation force that is not influenced by the system's states is said to be an ideal energy source. In real situations, a direct and feedback coupling between the excitation source and the system must always exist. This manifestation of the law of conversation of energy is known as Sommerfeld Effect. In the case of obtaining a mathematical model for such system, additional equations are usually necessary to describe the vibration sources and their coupling with the mechanical system. In this work, a cantilever beam and a non-ideal electric DC motor that is fixed to the beam free end is analyzed. The motor has an unbalanced mass that provides excitation to the system proportional to the current applied to the motor. During the motor's coast up operation, as the excitation frequency gets closer to the beam first natural frequency and if the drive power increases further, the DC motor speed remains constant until it suddenly jumps to a much higher value (simultaneously the vibration amplitude jumps to a much lower value) upon exceeding a critical input power. It was found that the Sommerfeld effect depends on some system parameters and the motor operational procedures. These parameters are explored to avoid the resonance capture in Sommerfeld effect. Numerical simulations and experimental tests are used to help insight this dynamic behavior.